2016
DOI: 10.1007/978-3-319-55970-4_1
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge-Grid Modelling for Academic Purposes

Abstract: Nowadays, we face a huge amount of data and information sharing on the Web by different users worldwide. A multidimensional perspective in describing a university ontology seems to be very important for the modelling of higher education resources. This paper proposes a multi-dimensional knowledge model, designed to distribute and manage knowledge resources efficiently. We propose our model as the foundation of an advanced knowledge platform including the following dimensions: time, area and social. Three cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…On the contrary, the latter has a verbal or written form (e.g. procedure) and is relatively easy to communicate, codify, store and distribute; usually, explicit representation uses a predefined notation that enables gathered (generated) knowledge to be expressed consistently and completely [3] (e.g. in the form of the association rule: if a customer buys wheat bread then he/she also buys skimmed milk, with support 0,02 and confidence 0,85).…”
Section: A Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the latter has a verbal or written form (e.g. procedure) and is relatively easy to communicate, codify, store and distribute; usually, explicit representation uses a predefined notation that enables gathered (generated) knowledge to be expressed consistently and completely [3] (e.g. in the form of the association rule: if a customer buys wheat bread then he/she also buys skimmed milk, with support 0,02 and confidence 0,85).…”
Section: A Knowledgementioning
confidence: 99%
“…In this case, "context" is often referred to as environment [7], location [8], or situation [9]. To these three nouns, we can respectively pin the following questions: (1) what resources are you surrounded by?, (2) where are you?, and (3) and if necessary may be identified "manually" by exploiting the expert (or domain knowledge), or "automatically" by using particular types of attributes [10].…”
Section: B Contextmentioning
confidence: 99%
“…In another work [8], we introduced the first multidimensional knowledge space model (including entityrelationship schema), implemented as a part of the developing system, designed to efficiently distribute and manage knowledge resources. We view our model as the foundation of a knowledge grid platform, where two significant aspects are considered: education-and researchdriven.…”
Section: Related Workmentioning
confidence: 99%
“…Knowledge management entails the following functions (Brewster, Ciravegna, & Wilks, 2002;Marwick, 2001;McQueen, 1998;Uren et al, 2006;Zins, 2007): information classification for proper understanding; sharing of ideas; promotion of collaboration among organizations; and standardization of information visà-vis easy retrieval. The works of scholars from a multitude of disciplines have suggested that access to a rich diversity of information encourages organisation existence and maintain growth (Owoc & Weichbroth, 2015;Wang & Ji, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been used in tertiary institutions of learning outside Nigeria to meet up with the challenges and vis-a-vis promotes knowledge-driven economy to ensure good quality, efficiency and ultimately leverage on competitive edge. Examples are: Mauritius (Abbass, 2017), Iran (Yokhaneha & Baghoumian, 2014), Europe (Owoc & Weichbroth, 2015), Asia (Wang & Ji, 2005), Kenya (Murumba & Micheni, 2017), etc. Many studies have also proven that modern knowledge sharing and management system such as knowledge grid (KG) is more effective than traditional ways of sharing and managing knowledge (Sani, 2015;Yokhaneha & Baghoumian, 2014).…”
Section: Introductionmentioning
confidence: 99%